1.3q-3.8-5.6q=-5.3q-4.3

Simple and best practice solution for 1.3q-3.8-5.6q=-5.3q-4.3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1.3q-3.8-5.6q=-5.3q-4.3 equation:


Simplifying
1.3q + -3.8 + -5.6q = -5.3q + -4.3

Reorder the terms:
-3.8 + 1.3q + -5.6q = -5.3q + -4.3

Combine like terms: 1.3q + -5.6q = -4.3q
-3.8 + -4.3q = -5.3q + -4.3

Reorder the terms:
-3.8 + -4.3q = -4.3 + -5.3q

Solving
-3.8 + -4.3q = -4.3 + -5.3q

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '5.3q' to each side of the equation.
-3.8 + -4.3q + 5.3q = -4.3 + -5.3q + 5.3q

Combine like terms: -4.3q + 5.3q = 1q
-3.8 + 1q = -4.3 + -5.3q + 5.3q

Combine like terms: -5.3q + 5.3q = 0.0
-3.8 + 1q = -4.3 + 0.0
-3.8 + 1q = -4.3

Add '3.8' to each side of the equation.
-3.8 + 3.8 + 1q = -4.3 + 3.8

Combine like terms: -3.8 + 3.8 = 0.0
0.0 + 1q = -4.3 + 3.8
1q = -4.3 + 3.8

Combine like terms: -4.3 + 3.8 = -0.5
1q = -0.5

Divide each side by '1'.
q = -0.5

Simplifying
q = -0.5

See similar equations:

| 130=10x+7y | | -14=-7m | | 4+9y-3=7y+43-4y | | 729p^2-36= | | .49x^2+12x=20 | | 15+10x+x^2=0 | | -21/4(-10)+80 | | 2h+1=-17 | | -10=10a | | 18x-12=22x+8 | | 3k=-12 | | 8-5x=-22 | | 8-5x=-22 | | 12.5*n=100 | | 4x^3-9x^2-x-6=0 | | -21/4(-10) | | 31=-7+x | | -21/4(10) | | 2(x+22)=5+3(x-2)-4x | | -3x8+4/(-2) | | r-45=-45 | | 9g+11=-2 | | 4xy^2+44x^2y^2-28xy^2=0 | | 3/4w=-16/27 | | 3/4s=-16/27 | | -16t^2+16=0 | | ab-9a+4b-36= | | -5(-3u+7)-3u=6(u-6)-7 | | -3=k+2 | | 2/3(1/8+4x)-3/8=5/8 | | 3a(x+7y)-b(x+7y)= | | s/3=5 |

Equations solver categories